Dialética da tolerância fiscal - Daniel Neto, Carlos Augusto (2014)
This dissertation sought to develop a critical and reflective study of the current theory of the Tax Law in Brazil, seeking to identify its problems and offer subsidies to their development. For this, it was developed a parallel between scientific paradigms that followed in recent history, the prevailing legal thought models in each scientific paradigms and those respective methods, to identify elements present from them in today's pragmatic of the Tax Law, and simultaneously demonstrate the delay of this relative to general scientific and philosophical thought. From there, it was sought the development of new bases for taxation thought, enabling the transition from a phenomenological tradition to an existentialist one, markedly by the assumption of a very material sense, closely related to liberty and human dignity without, however, forget the financial needs of the state. This existentialist model of Tax Law is based on the concept of fiscal tolerance, as a mutual understanding of the conflicting interests of all involved in the tax phenomenon, supporting himself, and being recursively sustained on four "pillars": a) ethical-axiological ; b) instrumental; c) hermeneutic; and d) systematic and normative. Finally, it is concluded that the existentialist model of tax thinking, called Dialectic of Fiscal Tolerance, beyond the ethical stance, involves a dialectical methodology between the problem and the system for making fair decisions, coupled with an awareness of the role of tax activity in relation to his own efficiency and public policies pursued by the State, and a systemic openness to its continuous development and improvement, always directed at the transformation of man-subject in a man-person